Carotenoid Thermostability Analysis and Tests on Unyil Corn - Puspita, Dhanang (University of Brawijaya, 2021)
Unyil corn is one of the varieties of corn cultivated by the community. Corn contains carotenoids which can be used as a source of vitamin A and antioxidants. Efforts are needed to find out the carotenoid content in corn so that it can be evaluated in its processing. The purpose of this study was to analyze the carotenoid content and thermostability of unyil corn. The method used is carotenoid isolation, corn processing by boiling, steaming, and making pop corn. Carotenoid analysis by scanning with a UV-Vis spectrophotometer. The results of the study, unyil corn contains carotenoids as big as 9.35 Î¼g / g. Unyil corn which is processed by boiling and steaming undergoes carotenoid degradation, while that which is processed into pop corn is still conserved at 3.09 Î¼g / g of the carotenoid. It can be concluded that unyil corn contains carotenoids and the thermostability is low.